Diabetes in young people in the Top End of the Northern Territory. Issue 11 (5th June 2013) - Stone, Monique; Baker, Alice; Maple Brown, Louise
Abstract : Aim: There is an increasing prevalence and burden of diabetes in young people, particularly Indigenous Australians. There have been no previous reports of the prevalence or burden of diabetes in young people in the Top End of the Northern Territory, a region of many risk factors for diabetes. Methods: This is a retrospective study of cases of diabetes in children and adults aged less than 25 years who were seen at Royal Darwin Hospital as inpatients or outpatients between 2007 and 2011. Results: From a population base of approximately 75 000 young people living north of Tenant Creek, there were 70 young people with type 1 diabetes (12 Aboriginal and/or Torres Strait Islander Australians) and 37 young people with type 2 diabetes (31 Aboriginal or Torres Strait Islander Australians). The median body mass index of those with type 2 diabetes was 28 kg/m 2, and only 29% had a body mass index >30 kg/m 2 . Overall, glycaemic control was poor. Conclusions: Rates of diabetes in young people in the Top End appear high. Case ascertainment and data collection were difficult for this study, highlighting the need for better database and systems for diabetes management.